A year right here : adventures with food and family in the great nearby - Thomson, Jess (University of Washington Press, 2017)
Armed with "The Here List" and a Type-A personality, Seattle-based writer and cookbook author Jess Thomson sets out to spend a year exploring the food of the Pacific Northwest with her family. Planning to revel in the culinary riches of the region and hoping to break her son, Graham, of his childhood pickiness, the adventures into the great nearby include building a backyard chicken coop, truffle hunting in Oregon, and razor clamming on the Washington coast. Her plans to spend "a year right here" are complicated by efforts to help Graham overcome some of the mobility limitations of cerebral palsy, and thwarted further by her own limitations that come to the fore when she attempts the "Gourmet Century," a hilly one-hundred-kilometer bike ride with gourmet food stops along the way.